2020
DOI: 10.1016/j.bjoms.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of remote OMFS assessments in the era of pandemic COVID-19 control measures

Abstract: Pandemic COVID-19 has put unprecedented pressure on NHS providers to offer non face-to-face consultation. This study aims to assess acceptability of patients and clinicians towards teleconsultation in oral and maxillofacial surgery compared with an expected face-to-face assessment. 340 telephone clinic patient episodes were surveyed over the initial 7-week period of pandemic-related service restriction. Appointment outcomes from a further 420 telephone consultations were additionally scrutinised. A total of 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Meanwhile, in the current study, acceptance of teleconsultations was not only high among physicians, but also, crucially, among patients. Moreover, most patients in this study would prefer teleconsultation over face-to-face visits in the future, which is consistent with results from other studies analysing ambulatory patients' preference for teleconsultations [10]. In another manuscript, teleconsultations were indicated as the most convenient form of receiving rheumatology advice by 82% of respondents [11].…”
Section: Resultssupporting
confidence: 90%
“…Meanwhile, in the current study, acceptance of teleconsultations was not only high among physicians, but also, crucially, among patients. Moreover, most patients in this study would prefer teleconsultation over face-to-face visits in the future, which is consistent with results from other studies analysing ambulatory patients' preference for teleconsultations [10]. In another manuscript, teleconsultations were indicated as the most convenient form of receiving rheumatology advice by 82% of respondents [11].…”
Section: Resultssupporting
confidence: 90%
“…In the study of Cronin et al [ 20 ] who aimed to explore patients and clinicians acceptability of teleconsultation performed via telephone appointment for different diagnostic groups in maxillofacial surgery practice compared with the in-person assessment they observed that 59.1% of the patients reported a strong preference for teleconsultation. However, clinicians rated 59.5% of remote consultations as requiring further review including the conditions like orthognathic surgery, TMD, salivary gland diseases, and head and neck cancer due to the inability to perform traditional face-to-face examination.…”
Section: Discussionmentioning
confidence: 99%
“…A low-priority examination might potentially conceal a severe disease, which has not been recognized by the general practitioner, or which has been underestimated by the patient. In such cases, teleconsultations offer a fundamental tool in allowing the specialist in maxillofacial surgery to raise the suspicion of disease, and subsequently intercept it (Cronin et al, 2020;Shanti et al, 2020). Moreover, in our experience, telemedicine has improved the exchange of information between colleagues across the region, leading to closer contact between specialists and general practitioners.…”
Section: Discussionmentioning
confidence: 88%